IDENTIFICATION OF ACTINOMYCETYES IN THE BIODEGRADED WALL MATERIAL BY PCR AMPLIFIED GENE FRAGMENT CODING FOR 16S rRNA - Arya, Garima; Kaushik, Purshotam (Journal of Drug Delivery and Therapeutics, 2012)
Generally, old buildings and monuments are often affected by biodecay. An inventory of the existing microbial consortia which associated with the damage part of the buildings wall is not yet integral part of the restoration process. This stems from the lack of effective means for such stocktaking. Although, Actinomycetes, fungi and bacteria cause severe damage through mechanical process from the growth into wall and its grounding and through their metabolism. Physiological and molecular approach based techniques were used in the detection and identification of DNA sequences encoding rRNA to actinomycetes present on building wall. DNA from isolate was extracted and 194 basepair fragments of the 16S rDNA were amplified with cultured primers. The 16S rDNA fragments of uniform length obtained from the different species were separated according to their sequences difference by PCR. By the sequencing excised and reamplified individual DNA bands, characterized the phylogenetic tree of corresponding actinomycetes. Using this approach, we identified members of the genera of Streptomyces, Nocardia and Micromonospora. Key words: Actinomycetes, Nocardia, Micromonospora, Streptomyces